Cultivares de milho e de feijão-caupi em cultivos puros e consorciados - Silva, Marcos Antônio Leite da (2017)
The objective of the study was to identify the best maize and cowpea cultivars, to be used in monoculture or intercropping, aiming at the production of green or dry grains. We used randomized block design, with six repetitions of eight treatments (four combinations and four monocultures corresponding). The yield of maize cultivars was not affected by cowpea cultivars. However, yield of dry cowpea was affected by maize cultivars. The yield of maize forage, the yield and green and dry seeds, of maize and cowpea were reduced in the consortium compared to monoculture. The cultivar AG 1051 was superior to the cultivar AL Bandeirante in the yield of green ears and grains, in the monocultures and intercropping. The cultivars of cowpea were equivalent in terms of yield of green beans and dry grains in the Intercropping, but the cultivar Corujinha was better than the cultivar Sempre Verde with respect to the yield of grains in monocultures. Monocultures provided higher yields than the consortia of the two evaluated crops. The AG 1051 + Corujinha combination provided land use efficiency in all combinations of immature fruits of the two crops. The combination AL Bandeirante + Sempre Verde was the only one to present efficiency